Pengaruh Metode Pengeringan Berbeda Terhadap Kadar Air, Kadar Abu, Dan Kadar Antioksidan Bubuk Daun Meniran (Phyllanthus niruri) - . Wahyu Maulidio, M; Putri Pamungkas, Pinctada (Politeknik Negeri Ketapang, 2025)
This study aims to determine the effect of different drying methods on water content, ash content, and antioxidant activity in meniran leaves (Phyllanthus niruri). The drying methods used were air drying for 2 days, sunlight for 20 hours, and oven for 3.5 hours at a temperature of 60℃. After drying, each sample was then analyzed to determine the water content, ash content, and IC_50 value for the antioxidant activity indicator. The results showed that the oven drying method produced the lowest water content of 6.11%, and the lowest ash content was obtained through air drying, which was 15%. While the highest antioxidant activity (the lowest IC_(50) value) was produced by samples dried in sunlight, which was 116.8429 µg/mL. From these results, it can be concluded that each drying method has a different effect on the characteristics of meniran leaves. Oven drying is suitable for reducing water content effectively, air drying maintains the lowest ash content, and sun drying is effective in maintaining antioxidant compounds. This study can be a reference in determining the appropriate drying method for processing meniran leaf herbal materials.